Development of a universal method for high yield of furfural and hydrogen from raw lignocellulosic biomass. (June 2022) - Lyu, Xiang
Abstract: In order to develop a universal method for the co-production of furfural and hydrogen from raw lignocellulosic biomass, three types of substrates (maple wood, wheat straw, and tall fescue) were investigated, integrating chemical and electrochemical technologies. The results show both furfural and pure hydrogen were produced from all the biomass substrates, and the substrate type, composition, concentration, and size all affected furfural and hydrogen production. The highest furfural production of 154 mg g −1 substrate was achieved from wheat straw. The highest conversion rate of 67% for the waste furfural residue was realized, and 335 ml pure hydrogen per gram of furfural residue with a Faradaic efficiency of 99.3% was obtained with a new electrolytic cell. A reaction mechanism for hydrogen evolution from furfural residue and a rule for co-production of furfural and hydrogen from raw biomass were proposed. The facts show that a promising universal method for the co-production of furfural and hydrogen from lignocellulosic biomass has been developed. Graphical abstract: Unlabelled Image Highlights: A method for high yield of furfural and H2 from lignocellulosic biomass was developed. The highest furfural production of 154 mg g −1 substrate was obtained from wheat straw. Faradaic efficiency of 99.3% for H2 evolution from waste furfural residue was achieved. A reaction mechanism for H2 evolution from waste furfural residue was proposed. A rule for furfural and hydrogen production from raw biomass was reported.